2022
DOI: 10.1177/0308518x221088294
|View full text |Cite
|
Sign up to set email alerts
|

The new whole state system: Reinventing the Chinese state to promote innovation

Abstract: This article joins interdisciplinary efforts to problematize dichotomous thinking (i.e. state vs. market, East vs. West, and new vs. old) in existing discourses concerning state capitalism. Focusing on the New Whole State System in relation to tech companies owned by Tsinghua University, we analyze the actually existing state capitalism in China as a spatiotemporally specific and conjuncturally situated assemblage of discourses, policies, and practices. We show that under both the Old Whole State System (1950s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…State-sponsored megaprojects, large-scale infrastructure and spatial planning strategies have been mobilized for territorial development and promotion, for integrating distant territories and facilitating the circulation of capital and for reconfiguring state sovereignty ( Kinossian and Morgan, 2023 ; Su and Lim, 2023 ; Szabó and Jelinek, 2023 ). New forms of territorialized policy interventions have been deployed in order to compete in high-tech sectors, develop frontiers of resource extraction, attract foreign investment, catalyze structural change and achieve a range of state spatial objectives ( Schindler et al, 2022 ; Wijaya and Camba, 2021 ; Zhang and Lan, 2023 ). Sovereign funds, state enterprises and other state-capital hybrids afford states the capacity to project geoeconomic power extra-territorially in transnational production, finance and digital networks ( McGregor and Coe, 2023 ; Rolf and Schindler, 2023 ).…”
Section: Territorializing the New State Capitalismmentioning
confidence: 99%
“…State-sponsored megaprojects, large-scale infrastructure and spatial planning strategies have been mobilized for territorial development and promotion, for integrating distant territories and facilitating the circulation of capital and for reconfiguring state sovereignty ( Kinossian and Morgan, 2023 ; Su and Lim, 2023 ; Szabó and Jelinek, 2023 ). New forms of territorialized policy interventions have been deployed in order to compete in high-tech sectors, develop frontiers of resource extraction, attract foreign investment, catalyze structural change and achieve a range of state spatial objectives ( Schindler et al, 2022 ; Wijaya and Camba, 2021 ; Zhang and Lan, 2023 ). Sovereign funds, state enterprises and other state-capital hybrids afford states the capacity to project geoeconomic power extra-territorially in transnational production, finance and digital networks ( McGregor and Coe, 2023 ; Rolf and Schindler, 2023 ).…”
Section: Territorializing the New State Capitalismmentioning
confidence: 99%
“…Compared to TMSC, UNIS entered the semiconductor market much later, but it has become a rising force and is expanding rapidly. After 2009, when Zhao Weiguo became CEO of Unisplendour, the company entered the semiconductor market; however, it was later revealed that Zhao's primary business income was derived from the expansion of the real estate industry (Zhang & Lan, 2022); since then, Unisplendour has grown incredibly quickly in this industry by acquiring numerous other corporations. In June 2013, UNIS acquired Spreadtrum Communications, which was ranked first in China and third in the world in the field of mobile communication baseband chip design.…”
Section: Swot Analysis Of Tsmcmentioning
confidence: 99%
“…In many ways, these articles engage what might be considered to be standard topics in new state capitalism studies – including sovereignty, state-owned enterprises, China, inter-state rivalries in the global economy, crises and market intervention – but they do so by mobilizing some of the signature contributions of critical political economy and economic geography, such as theories of the state in capitalism (Alami and Dixon, 2023; Paul and Cumbers, 2023; Silverwood and Berry, 2023), the role of market failure in policy making (Palcic et al, 2023; Paul and Cumbers, 2023), and the scalar relations implicit in sovereignty claims and national state services for the global economy (Eagleton-Pierce, 2023; Silverwood and Berry, 2023; Zhang and Lan, 2023).…”
mentioning
confidence: 99%
“…Conceptual modifications are offered across the theme issue, such as uneven and combined state capitalism (Alami and Dixon, 2023), reluctant state capitalism (Palcic et al, 2023), financial state capitalism (Silverwood and Berry, 2023) and authoritarian state capitalism (Kinossian and Morgan, 2023). Likewise, the new state capitalism is propelled into unexplored areas even within operating environments quite familiar in the literature, such as by questioning the nature and extent of state capitalism associated with the actually existing complexities of the Chinese state, including the financialization of development projects (Su and Lim, 2023; Zhang and Lan, 2023), and the role of capital markets in emerging market economies (Petry et al, 2023). This testifies to the malleability and capacious character of the category itself: the new state capitalism can be molded in specific ways by bringing it into conversation with other concepts (or with the addition of a qualifier), and it can be pushed into new directions by stretching its empirical and spatiotemporal domains of application, according to different analytical objectives and priorities.…”
mentioning
confidence: 99%
See 1 more Smart Citation